Pengaruh Prenatal Yoga dalam Mengurangi Kecemasan pada Kehamilan: Systematic Literature Review - Cindy Ria Aprilia Putri; Lisa Trina Arlym; Yocki Yuanti (Universitas Baiturrahim, 2022)
Such as anxiety, various complications can occur in labor and hinder labor. Anxiety of pregnant women can be overcome with one of the complementary therapies, namely prenatal yoga. The purpose of this study was to analyze and review journals related to the effect of prenatal yoga on anxiety in pregnant women. This type of research is a Systematic Literature Review by searching for journals using the Google Scholar, ProQuest, PubMed, and Garuda databases from 2016 – 2021 and the literature selection process using PRISMA diagrams with a Quasy Experimental research design. The results showed that seven out of 9 articles experienced mild anxiety after doing prenatal yoga. Six out of 9 articles doing prenatal yoga twice a week can reduce anxiety. The conclusion of this study is that prenatal yoga is very effective in reducing anxiety in TM III pregnancy. Prenatal yoga which is done twice a week can reduce discomfort during pregnancy, provide comfort so that it can reduce anxiety in TM III pregnant women.